Consumptive Patterns and Cultural Hedonism of the Muslim Millennial Generation in Terms of an Islamic Economic Perspective - Siti Mujiatun (Lembaga Riset Ilmiah, 2023)
This research washes away about pattern consumptive and generational hedonism culture millennials Islam reviewed fthe rom perspective Islamic economics. This research is study descriptive, where something incident or phenomenon described to get results are accurate and interpreted using words accurately written. The author uses type study literature that is method scientifically systematic covering the collection of ingredients literature related to the goal research. Research results conclude that Islam has make consumption is important Because when a Muslim consumes good things, it brings blessings in his life. If economic capitalist make happiness as a goal end activity economy to create attitude hedonism, then Islamic economics does not do it. Make Benefit as the key the happiness of the world and the hereafter. Shop in Islam do only with intention worship to Allah SWT. Generation the biggest millennials influence to trends, especially fashion, must be capable enter habit consumption Islamic economics to in his life without excessive in spend treasure and always remember that Treasure own the rights of others and always limit self. so that No affected by trends moment this. happen with prioritize what is needed and eliminates what is wanted or not really required